Hypoxic environment promotes barrier formation in human intestinal epithelial cells through regulation of microRNA 320a expression - Münchau, Stephanie; Deutsch, Rosalie; Castro, Ines J. de; Hielscher, Thomas; Niesler, Beate; Lusic, Marina; Stanifer, Megan; Boulant, Steeve (Molecular and cellular biology, 2019)
Intestinal epithelial cells (IECs) are exposed to the low-oxygen environment present in the lumen of the gut. These hypoxic conditions on one hand are fundamental for the survival of the commensal microbiota and, on the other hand, favor the formation of a selective semipermeable barrier, allowing IECs to transport essential nutrients/water while keeping the sterile internal compartments separated from the lumen containing commensals. The hypoxia-inducible factor (HIF) complex, which allows cells to respond and adapt to fluctuations in oxygen levels, has been described as a key regulator in maintaining IEC barrier function by regulating their tight junction integrity. In this study, we sought to better evaluate the mechanisms by which low oxygen conditions impact the barrier function of human IECs. By profiling miRNA expression in IECs under hypoxia, we identified microRNA 320a (miRNA-320a) as a novel barrier formation regulator. Using pharmacological inhibitors and short hairpin RNA-mediated silencing, we could demonstrate that expression of this microRNA (miRNA) was HIF dependent. Importantly, using overexpression and knockdown approaches of miRNA-320a, we could confirm its direct role in the regulation of barrier function in human IECs. These results reveal an important link between miRNA expression and barrier integrity, providing a novel insight into mechanisms of hypoxia-driven epithelial homeostasis.
Gesehen am 30.07.2019